Reninoma as a cause of severe hypertension and poor pregnancy outcome in young woman - Stamenković-Pejković, Danica; Šumarac-Dumanović, Mirjana; Bojanić, Nebojša; Marković-Lipkovski, Jasmina; Vještica, Jelena; Ivanović, Aleksandar; Cvijović, Goran; Gligić, Ana; Bumbaširević, Uroš; Jelić, Svetlana; Polovina, Snežana; Micić, Dragan (Vojnosanitetski pregled, 2017)
Introduction. Juxtaglomerular cell tumor (JGCT) or reninoma is a very rare cause of curable hypertension among young people. The early diagnosis is the most important based on the clinical presentation, hormonal and radiological findings observed on computed tomography (CT) and/or magnetic resonance imaging (MRI). The final confirmation of the JGCT is the lateralization of the plasma renin activity (PRA) during the selective renal venous sampling. Case report. This report presents a typical case of young women with JGCT which was manifested for the first time with severe hypertension during the pregnancy and was the reason of fetal death. After the miscarriage, the diagnosis of JGCT was made by the CT scanning and confirmed by the selective renal venous sampling. After the partial nephrectomy, the blood pressure and serum potassium normalized without the medications. Conclusion. Reninoma should be considered in the differential diagnosis as a cause of severe hypertension in pregnancy and also should be suspected in young hipertensives (especially females) with hypokalemia and secondary hyperaldosteronism after the exclusion of other causes particularly renal artery stenosis. A dynamic contrast-enhanced CT, MRI and selective renal venous sampling are the most important tools in the diagnosis of JGCT.
Keywords: juxtaglomerular apparatus; kidney neoplasms; hypertension; fetal death; diagnostic techniques and procedures; diagnosis; differential; urologic surgical proceduresurologic surgical procedures